Properties of Particleboard made from Petung Bamboo (Dendrocalamus asper) and Wulung Bamboo (Gigantochloa atroviolacea) Particles with Extraction Treatment - Ragil Widyorini; Ikhwan Syahri; Greitta Kusuma Dewi (Jurnal Ilmu Kehutanan)
Bamboo has extractives, which the percentage of extractive was different based on bamboo species. This research aimed to investigate the effect of extraction treatment at different bamboo species on the particleboard properties. Two types of bamboo were used, i.e. Petung bamboo (Dendrocalamus asper) and Wulung bamboo (Gigantochloa atroviolacea). Three extraction treatments were conducted to the bamboo particles before the particleboard manufacture, i.e. unextracted, cold-water extraction, and hot-water extraction. The particleboard was made in the size of 25 cm x 25 cm x 0.7 cm, target density of 0.9 g/cm³, citric acid content of 30%, and pressing temperature of 180°C for 10 min. The results showed that the interaction between extraction treatment and bamboo species significantly affected on the water absorption and internal bond strength, however bamboo species affected significantly on the moisture content, modulus of rupture, and modulus of elasticity. All of particleboards could met the requirement of the 13 type of Japanese Industrial Standard (JIS) A 5908. In this research, particleboards made from wulung bamboo particles without extraction treatment have properties that met the requirement of the 18 type and the products have potential to be as exterior materials for furniture. In general, an extraction treatment was not an important step on the manufacturing of bamboo particleboard using citric acid 30% as adhesive. However, the extraction treatment could increase significantly the internal bond strength of particleboard made from petung bamboo.